2017
DOI: 10.1016/j.bbadis.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Copper therapy reduces intravascular hemolysis and derepresses ferroportin in mice with mosaic mutation ( Atp7a mo-ms ): An implication for copper-mediated regulation of the Slc40a1 gene expression

Abstract: Mosaic mutant mice displaying functional dysfunction of Atp7a copper transporter (the Menkes ATPase) are an established animal model of Menkes disease and constitute a convenient tool for investigating connections between copper and iron metabolisms. This model allows to explore changes in iron metabolism in suckling mutant mice suffering from systemic copper deficiency as well as in young and adult ones undergone copper therapy, which reduces lethal effect of the Atp7a gene mutation. Our recent study demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…In many hemolytic disorders, excessive hemolysis may overwhelm endogenous plasma haptoglobin/hemopexin and other scavenging mechanisms as well as heme degradation pathways in hepatic, splenic and bone marrow macrophages. Human 9 and animal 10,11 studies have clearly shown that under severe hemolytic conditions, the kidneys participate in the management of heme and non-heme iron released from disrupted RBCs. There is growing evidence that renal tubular cells can adapt to exposure to high levels of heme by inducing HO1 and ferritin 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In many hemolytic disorders, excessive hemolysis may overwhelm endogenous plasma haptoglobin/hemopexin and other scavenging mechanisms as well as heme degradation pathways in hepatic, splenic and bone marrow macrophages. Human 9 and animal 10,11 studies have clearly shown that under severe hemolytic conditions, the kidneys participate in the management of heme and non-heme iron released from disrupted RBCs. There is growing evidence that renal tubular cells can adapt to exposure to high levels of heme by inducing HO1 and ferritin 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Kidney is an organ highly adapted to reabsorb both non-heme and heme iron filtered in the glomerulus to the primary urine and to recirculate it across epithelial cells of proximal tubules into the blood stream [ 14 ]. Under intravascular hemolysis conditions, such as chronic hereditary and acquired hemolytic anemias, kidneys participate in the management of iron released from disrupted erythrocytes to the blood plasma [ 27 , 28 , 29 , 30 ]. It is clear that the structural and functional maturity of the kidneys is indispensable for this process.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mutations in the human ATP7A gene lead to a neurological disorder called Menkes disease, which usually results in mortality at 3-5 years of age in its classical form (16). The mouse ATP7A protein is encoded by the X-linked Atp7a gene, and among its several reported mutations in mice, one (Atp7a mo-ms ) results in the mottled phenotype resembling Menkes disease and affects mosaic mutant males (15,34). In these mice, similarly to patients with Menkes disease, copper accumulates in the small intestine (trapped in enterocytes) and kidneys, while liver, brain, and heart display its deficiency (34).…”
Section: Introductionmentioning
confidence: 99%
“…The mouse ATP7A protein is encoded by the X-linked Atp7a gene, and among its several reported mutations in mice, one (Atp7a mo-ms ) results in the mottled phenotype resembling Menkes disease and affects mosaic mutant males (15,34). In these mice, similarly to patients with Menkes disease, copper accumulates in the small intestine (trapped in enterocytes) and kidneys, while liver, brain, and heart display its deficiency (34). Additionally, as in the classical form of Menkes disease, the mosaic mutation of Atp7a leads to early death on about day 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation